Implementasi Metode SMART dan MOORA Pada Operasional Hibah Peralatan Olahraga - Gunawan, Jaka; Samsudin, Samsudin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Advances in information technology have brought significant changes in various aspects of human life, including decision making. Making decisions by utilizing technology makes the decision-making process run more quickly and accurately. This research proposes the development of a decision support system to select prospective recipients of sports equipment effectively and fairly at the North Sumatra Youth and Sports Service, using the SMART (Simple Multi Attribute Rating Technique) method which is used to determine the criteria and weight of the data, and the MOORA (Multi -Objective Optimization on the Basis of Ratio Analysis) is a multi-attribute decision making method that makes it easier to calculate alternative values which have more accurate and targeted results in helping decision making. The research stage involves observation, interviews, and literature study. 5 criteria were used in this research, including productivity, achievement, secretariat location, training program, and equipment requirements. Data on prospective recipients of sports equipment used for analysis was 10 data. Through the SMART and MOORA methods, the system gives the best ranking to the alternative that best meets the predetermined criteria. The ranking results show that the prospective recipient of sports equipment is Sahabat Muda Badmintoon with rank 1 with a score of 0.8 using the SMART method and a score of 0.044 using the MOORA method. The SMART and MOORA methods show the potential to be used as tools to help make decisions about receiving sports equipment more efficiently and fairly.